Enterobacter gergoviae peritonitis in a patient on chronic ambulatory peritoneal dialysis - first reported case - Abdul Rashid, Anna Misya'il; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Enterobacter gergoviae is a gram negative rod-shaped opportunistic organism reported to cause urinary and respiratory tract infections, but peritonitis caused by this organism is unknown. We report a case of 50-year-old patient on peritoneal dialysis (PD) presented with Enterobacter gergoviae peritonitis with septic shock. Despite Intraperitoneal (IP) cloxacillin 250mg qid and IP ceftazidime 1gram q24h and subsequent escalation with IP amikacin 2mg/kg q24h and IP vancomycin 15mg/kg q24h within the next 48 hours, his peritonitis remained refractory and required catheter removal. Although Enterobacter gergoviae is naturally sensitive to aminoglycosides, carbapenems and quinolones, it reacts differently to the beta lactam antibiotics. Their resistance to third-generation cephalosporins is fast emerging and treatment with third-generation cephalosporins may cause AmpC-overproducing mutants. The majority of Enterobacteriaceae, including Extended-spectrum beta-lactamases producers, remain susceptible to carbapenems. Our report provides an unfavourable course of E. gergoviae peritonitis likely due to acquired secondary drug resistance during the therapy period.